Factors affecting consumers’ willingness to purchase telehomecare products - Jakkreeporn Sannork (2018)
© Springer International Publishing Switzerland 2016. This paper investigated the influence of various factors-product knowledge and perceived risk, benefit, and value-on consumers’ willingness to purchase telehomecare products (e.g., the RFID smart care watch). Of the 500 returned questionnaires, 388 were valid (77.60 %). Structural equation modeling (SEM) was used as the main research method. The results showed that the perceived risk of telehomecare products by consumers had a significant impact on perceived value, but it had no significant impact on willingness to purchase. In contrast, product knowledge significantly influenced the perceived benefit of the product and consumers’ willingness to buy.